MT-DIPS: a new data duplication integrity protection scheme for multi-tenants sharing storage in SaaS. (2018) - Li, Lin; Zhang, Yongxin; Ding, Yanhui
In SaaS, the data sharing storage mode and tenant isolation requirement present new challenge to traditional remote data duplication protection schemes. This paper aims at the new requirement of tenant data duplication protection in SaaS and presents a tuple sampling-based tenant duplication protection mechanism MT-DIPS (Duplication Integrity Protection Scheme for Multi-Tenants). Instead of data block sampling, MT-DIPS accommodates the data isolation requirement of different tenants by sampling tenants physical data tuples. Through periodical random sampling, MT-DIPS reduces the complexity on service provider side of verification object construction and eliminates the resource waste. Analysis and the experimental results show that if the damage rate of tenant data tuples is about 1%, the random sampling data number is about 5% of the total number of tuples. MT-DIPS makes use of homomorphism labels with auxiliary authentication structure to allow trusted third party verification without disclosing tenant data to relieve the verification burden on tenants' client sides.